2003
DOI: 10.1046/j.1468-3083.2003.00603.x
|View full text |Cite
|
Sign up to set email alerts
|

Indolent systemic mast cell disease: immunophenotypic characterization of bone marrow mast cells by flow cytometry

Abstract: The use of flow cytometry on bone marrow samples from patients with mastocytosis reveals immunophenotypic differences that can serve to allow classification of these subjects in the category of indolent SMCD even though involvement of another organ system may not be thoroughly confirmed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 21 publications
1
4
0
1
Order By: Relevance
“…Since in the early stages of the disease, indolent systemic mastocytosis patients usually display very low mast cell burden in the absence of bone marrow mast cells aggregates, demonstration of the presence of either clonal or phenotypically aberrant mast cells in the bone marrow and/or other tissues by highly sensitive methods becomes essential. In line with other reports, the presence of CD25 bright þ bone marrow mast cells appeared to be a highly specific diagnostic criteria being found in most systemic mastocytosis patients, 19,25,[35][36][37][38][39] but in only a few control bone marrow samples, all of which corresponded to FIP1L1/PDGFRA þ chronic eosinophilic leukemia and myelodisplastic syndrome, in line with previous observations; 10 altogether these findings support the usage of CD25 expression on bone marrow mast cells as a surrogate marker for mast cells clonality. Noteworthy, the presence of clonal mast cells assessed through KIT mutation or a clonal HUMARA test (in bone marrow mast cells from women lacking KIT mutations) in highly purified mast cells was found in virtually every case (94%), confirming previous observations; 18,27 this indicates that KIT mutation in bone marrow mast cells may have a higher diagnostic value than other WHO criteria.…”
Section: Discussionsupporting
confidence: 90%
“…Since in the early stages of the disease, indolent systemic mastocytosis patients usually display very low mast cell burden in the absence of bone marrow mast cells aggregates, demonstration of the presence of either clonal or phenotypically aberrant mast cells in the bone marrow and/or other tissues by highly sensitive methods becomes essential. In line with other reports, the presence of CD25 bright þ bone marrow mast cells appeared to be a highly specific diagnostic criteria being found in most systemic mastocytosis patients, 19,25,[35][36][37][38][39] but in only a few control bone marrow samples, all of which corresponded to FIP1L1/PDGFRA þ chronic eosinophilic leukemia and myelodisplastic syndrome, in line with previous observations; 10 altogether these findings support the usage of CD25 expression on bone marrow mast cells as a surrogate marker for mast cells clonality. Noteworthy, the presence of clonal mast cells assessed through KIT mutation or a clonal HUMARA test (in bone marrow mast cells from women lacking KIT mutations) in highly purified mast cells was found in virtually every case (94%), confirming previous observations; 18,27 this indicates that KIT mutation in bone marrow mast cells may have a higher diagnostic value than other WHO criteria.…”
Section: Discussionsupporting
confidence: 90%
“…8,9,13,15,16 Among other markers, aberrant expression of CD2 and CD25 was highlighted as a potential hallmark of systemic mastocytosis, as both proteins were absent in normal/reactive bone marrow mast cells while coexpressed in the great majority of systemic mastocytosis patients. 8,13,17 Further studies confirmed these findings and at the same time they showed that among the two markers, CD25 could be more sensitive and reliable than CD2 as positivity for the later marker largely depends on the sensitivity of the fluorochromeconjugated antibody reagent used with sensitivity rates of 67% and 87% for CD2-FITC and CD2-PE reagents, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…(Source: Bodni et al, 2003;Diaz-Agustin et al, 1999;Escribano et al, 1995Escribano et al, , 1997Escribano et al, , 1998bEscribano et al, , 1998cEscribano et al, , 1998dEscribano et al, , 1999Escribano et al, , 2001Escribano et al, , 2002Escribano et al, , 2006Nun˜ez et al, 2002;Orfao et al, 1996;Pardanani et al, 2004;Teodosio et al, 2010;Valent et al, 2001b. (Source: Bodni et al, 2003;Diaz-Agustin et al, 1999;Escribano et al, 1995Escribano et al, , 1997Escribano et al, , 1998bEscribano et al, , 1998cEscribano et al, , 1998dEscribano et al, , 1999Escribano et al, , 2001Escribano et al, , 2002Escribano et al, , 2006Nun˜ez et al, 2002;Orfao et al, 1996;Pardanani et al, 2004;Teodosio et al, 2010;Valent et al, 2001b.…”
Section: Activated MC Immunophenotypeunclassified
“…Early studies on the immunophenotypic features of BM MC in SM reported several aberrant phenotypes that allow a clear discrimination from normal and reactive MC (Bodni et al, 2003;Escribano et al, 1995Escribano et al, , 1997Escribano et al, , 1998cEscribano et al, , 1999Escribano et al, , 2001Escribano et al, , 2002Pardanani et al, 2004) (Table VI). These early studies reported aberrant expression for CD2 and CD25 as a hallmark for SM, since both these proteins were absent in normal/reactive BM MC, but expressed in the great majority of SM patients (Escribano et al, 1995(Escribano et al, , 1997(Escribano et al, , 1998c.…”
Section: Immunophenotypic Characteristics Of Bm MC In Systemic Masmentioning
confidence: 99%